Taxpayers Comply in Paying Land and Building Taxes (Case Study in Lamongan Regency) - Putro, Guruh Marhaenis Handoko; Devi Febrianti; Amrizal Imawan; Ira Megasyara; Ninik Mas'adah; Suryani Yuli Astuti (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2024)
Taxes are one of the largest sources of state income. All citizens will benefit from the tax function. Recently, a lot of tax fraud has emerged among taxpayers. This research aims to determine the influence of understanding, level of trust in the government, community income, awareness and tax sanctions on taxpayer compliance in paying land and building taxes in Lamongan Regency. Lamongan Regency The object of this research is a village in Lamongan Regency. This research was conducted on 100 respondents using a simple random sampling method, namely Land and Building Taxpayers. This research uses a quantitative descriptive approach with associative research methods. Data collection was carried out by distributing questionnaires and data analysis using multiple linear regression. The research results show that the variables of understanding, level of trust in the government, and tax sanctions have no effect on taxpayer compliance in paying PBB, while people's income and awareness influence taxpayer compliance in paying PBB.